Development of a NS2B/NS3 protease inhibition assay using AlphaScreen® beads for screening of anti-dengue activities - Abduraman, Muhammad Asyraf; Hariono, Maywan; Yusof, Rohana; Abd Rahman, Noorsaadah; Wahab, Habibah A.; Tan, Mei Lan (Elsevier, 2018)
Background: Dengue infection is an endemic infectious disease and it can lead to dengue fever, dengue hemorrhagic fever, and/or dengue shock syndromes. Dengue NS2B/NS3 protease complex is essential for viral replication and is a primary target for anti-dengue drug development. In this study, a NS2B/NS3 protease inhibition assay was developed using AlphaScreen ® beads and was used to screen compounds for their protease inhibition activities. Methods: The assay system utilized a known NS2B/NS3 peptide substrate, a recombinant of NS2B/NS3 protease with proprietary StrepTactin ® donor and nickel chelate acceptor beads in 384-well format. Results: The optimized assay to screen for NS2B/NS3 protease inhibitors was demonstrated to be potentially useful with reasonable zʹ factor, coefficient variance and signal to background ratio. However, screening of synthesized thioguanine derivatives using the optimized AlphaScreen ® assay revealed weak NS2B/NS3 inhibition activities. Conclusion: The AlphaScreen ® assay to screen for NS2B/NS3 protease inhibitors is potentially applicable for high throughput screening.